2021
DOI: 10.1097/ncq.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Through Their Eyes

Abstract: Background: Personal protective equipment (PPE) plays a critical role in protecting health care workers (HCWs). During the coronavirus disease-2019 (COVID-19) pandemic, shortages of PPE supplies drastically changed the way PPE was obtained and used by HCWs. Purpose: The objective was to investigate the impact of the COVID-19 pandemic and patient isolation type on PPE compliance. Methods: This investigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Ainda, em relação ao uso de EPIs, houve o receio das crianças internadas para com os profissionais utilizando máscaras. O uso desses acessórios esconde a expressão facial dos membros da equipe, e a criança não consegue visualizar o rosto do trabalhador que está cuidando, podendo gerar medo e ansiedade (10,11) , aumentando o desconforto no período da hospitalização.…”
Section: Uma Criança Com Esquizofrenia [] Geralmente Eles Enxergam Im...unclassified
See 1 more Smart Citation
“…Ainda, em relação ao uso de EPIs, houve o receio das crianças internadas para com os profissionais utilizando máscaras. O uso desses acessórios esconde a expressão facial dos membros da equipe, e a criança não consegue visualizar o rosto do trabalhador que está cuidando, podendo gerar medo e ansiedade (10,11) , aumentando o desconforto no período da hospitalização.…”
Section: Uma Criança Com Esquizofrenia [] Geralmente Eles Enxergam Im...unclassified
“…Além de a temática ser relevante no contexto acadêmico, a condução deste estudo é justificada, pois observou-se uma lacuna do conhecimento devido à escassez de materiais que abordassem o tema sobre cuidado de enfermagem à criança com transtornos mentais em leitos destinados à psiquiatria na unidade de internação pediátrica, a partir da ótica dos enfermeiros, em um único estudo. Nesse contexto, apenas foram encontradas pesquisas que abordassem as repercussões da pandemia na saúde mental de crianças (2,6,7,8,(9)(10)(11) , cuidado de enfermagem em unidades psiquiátricas infantis (1,(3)(4)(5) , e repercussão dos cuidados de enfermagem com crianças hospitalizadas na pediatria (12,13,14) .…”
Section: Introductionunclassified
“…Still, regarding the use of PPE, there was a fear of hospitalized children towards professionals using masks. The use of these devices hides the facial expressions of the team members, and the child is unable to visualize the face of the worker caring for, which can generate fear and anxiety (10,11) , increasing discomfort during the hospitalization period.…”
Section: There Was the Use Of The Mask That Hides Us And We End Up No...mentioning
confidence: 99%
“…In addition to the theme being relevant in the academic context, conducting this study is relevant as a knowledge gap was observed due to the lack of materials that addressed the topic of nursing care for children with mental disorders in beds intended for psychiatry in the pediatric inpatient unit, from the perspective of nurses, in a single study. In this context only studies that addressed the repercussions of the pandemic on the mental health of children (2,6,7,8,(9)(10)(11) , nursing care in child psychiatric units (1,(3)(4)(5) , and the impact of nursing care for hospitalized children in pediatrics were found (12,13,14) .…”
Section: Introductionmentioning
confidence: 99%